(untitled) (The Review of Diabetic Studies, 2025)
Background: The rapid digitalization of healthcare has transformed nursing practice, care delivery, and organizational processes. Nurses are central to the adoption and sustained use of digital health technologies; however, the success of digital transformation initiatives largely depends on effective leadership. Emerging evidence suggests that inadequate leadership preparation, limited digital literacy among nurse leaders, and insufficient alignment between technology and clinical workflows can hinder digital transformation in nursing. A comprehensive synthesis of leadership-related evidence is therefore essential to guide practice, education, and policy. Aim: This systematic review aimed to examine the roles, competencies, and leadership approaches that support digital transformation in nursing practice within healthcare settings. Method: A systematic review design was employed. Peer-reviewed studies published between 2021 and August 2025 were identified through multiple electronic databases. Following a structured screening and selection process, ten studies were included for detailed analysis. Data were extracted and synthesized using a narrative and thematic approach, focusing on leadership competencies, organizational support, technology adoption, and barriers to digital transformation in nursing. Results: The findings revealed that leadership competence, particularly digital literacy and e-leadership skills, was a key enabler of successful digital transformation in nursing. Nurse leaders influenced technology adoption by facilitating training, supporting user-centered implementation, and aligning digital systems with clinical workflows. Organizational support and leadership involvement in governance further strengthened digital initiatives. However, persistent challenges such as resistance to change, limited leadership preparedness, and insufficient participation of nursing leaders in digital policy development were identified across studies. Conclusion: The review highlights leadership as a critical driver of digital nursing transformation. Strengthening digital leadership competencies among nurse leaders is essential for achieving sustainable, nurse-centered digital healthcare systems. Targeted leadership development and greater involvement of nurses in digital governance are recommended to enhance future digital transformation efforts.